Bone marrow evaluation in a pediatric population with pancytopenia in a tertiary care children’s hospital of Nepal (Journal of Pathology of Nepal, 2024)
Background: Pancytopenia, which is characterized by a triad of anemia, leukopenia, and thrombocytopenia, is frequently observed among the pediatric population. This study was carried out to determine the common etiologies of pancytopenia in children through bone marrow aspiration examination.Materials and methods: A one-year retrospective cross-sectional study of 64 cases of pancytopenia in the pediatric population was conducted at the Department of Pathology, Kanti Children’s Hospital, from July 2019 to June 2020.Results: 64 (35.55%) cases underwent bone marrow examination for pancytopenia. The patients' ages ranged from 4 months to 14 years, with a median age of 6.24±1.12 years. The majority of the patients fell into the age group of 1-5 years. The most common cause of pancytopenia was acute leukemia and hypoplastic bone marrow followed by erythroid hyperplasia, leishmaniasis, and megaloblastic anemia.Conclusions: Bone marrow examination is the fundamental diagnostic modality to diagnose the majority of cases of pancytopenia. It is important to consider acute leukemia, hypoplastic bone marrow, and leishmaniasis into account when evaluating pancytopenia in pediatric patients.